Kemampuan Kijing Lokal (Pilsbryoconcha exilis) Mereduksi Limbah Organik Budidaya Ikan Sidat (Anguilla sp.) - Dudi Muhammad Wildan; Ridwan Affandi; Niken Tunjung Murti Pratiwi (Musamus Fisheries and Marine Journal, 2021)
The release of organic waste into the waters due to the Eel (Anguilla sp.) rearing activity will cause eutrophication. Efforts to reduce organic waste can be done by using local mussel (Pilsbryoconcha exilis) because it has biofiltration capabilities. The purpose of this study was to determine the ability of local mussels in reducing organic waste. The research design used in this study was a randomized block design (RBD), with treatment in the form of differences in waste concentration (50% and 100%), while the group was in the form of differences in the size of the gravestone (small, medium, and large). The results showed that mussel was able to reduce organic matter, the effective time of local mussel (P. exilis) to reduce organic waste from the cultivation of eel (Anguilla sp.) Was in the first 6 days. The most effective treatment is the use of 100% waste concentration and small mussel. This treatment was able to reduce COD values ​​by 66.1 mg/L (28%), turbidity by 187.2 NTU (16%), TSS by 134 mg/L (36%), and ammonia by 0.004 mg/L (24%), and increased biomass by 7.21 grams (3%).